2000
DOI: 10.1007/s002480000010
|View full text |Cite
|
Sign up to set email alerts
|

Sesbania herbacea–Rhizobium huautlense Nodulation in Flooded Soils and Comparative Characterization of S. herbacea-Nodulating Rhizobia in Different Environments

Abstract: The nodulation of S. herbacea was compared under flooded and non-flooded conditions in two different soils. One soil was from a flooded field in Sierra de Huautla, the native habitat of this legume, while the other soil was from a well-drained field in Cuernavaca, where rhizobia were found to nodulate the introduced S. herbacea plants. Nodulation of the plants was completely eliminated by flooding in the Cuernavaca soil, whereas nodules were obtained in the same soil under non-flooded conditions. In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Rheinheimera chrinomii was first cultivated from eggs of Chironomidae larvae (Halpern et al, 2007), which are dominating the macrobenthos in the sediment of Lake Balaton (Dévai, 1990;Specziár, 2008). Closest relatives of the isolates among Alphaproteobacteria, have been characterized in association with a diversity of habitats including plant-associations (Rhizobium huautlense, Agrobacterium tumefaciens, Ensifer adhaerens) (Wang & Martínez-Romero, 2000), terrestrial and aquatic (Sphingomonas spp., Mycoplana bullata) (Long et al, 2009) environments. Most species of Actinobacteria are typical for soils and aquatic environments (Nold & Zwart, 1998;Felske et al, 1999;Warnecke, et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Rheinheimera chrinomii was first cultivated from eggs of Chironomidae larvae (Halpern et al, 2007), which are dominating the macrobenthos in the sediment of Lake Balaton (Dévai, 1990;Specziár, 2008). Closest relatives of the isolates among Alphaproteobacteria, have been characterized in association with a diversity of habitats including plant-associations (Rhizobium huautlense, Agrobacterium tumefaciens, Ensifer adhaerens) (Wang & Martínez-Romero, 2000), terrestrial and aquatic (Sphingomonas spp., Mycoplana bullata) (Long et al, 2009) environments. Most species of Actinobacteria are typical for soils and aquatic environments (Nold & Zwart, 1998;Felske et al, 1999;Warnecke, et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…They form root-and/or stem-nodules with rhizobia via crack entry and determinate nodules under hydrogen conditions, however, they are also invaded by root hair infection and form both indeterminate and determinate nodules in non-flooded soil or vermiculite [7]. To date, nodulation of up to 40 Sesbania species has been reported after infection with symbiotic nitrogen-fixing bacteria, commonly called rhizobia [11], including Neorhizobium huautlense and other Rhizobium, Mesorhizobium and Ensifer (formerly Sinorhizobium) species associated with Sesbania herbacea [51,52]; Azorhizobium caulinodans and Bradyrhizobium sp. with S. rostrata [12,13,15]; A. doebereinerae with S. virgate [16]; Ensifer teranga and E. saheli with S. rostrate and S. cannabina [12]; Mesorhizobium plurifarium with S. punicea, S. sericea and S. herbacea; N. huautlense with S. sericea and S. exasperate [48,53]; Rhizobium gallicum with S. sericea and S. sesban.…”
Section: Introductionmentioning
confidence: 99%
“…They stimulate root growth of various crop plants (Belimov et al 2001;). This mechanism is most effective on plants that are more susceptible to the effects of ethylene especially under such stress conditions as flooding (Grichko and Glick 2001), drought (Lucy et al 2004) and phytopathogens (Wang et al 2000). It has been shown that the bacterial ACC deaminase is not induced in cells grown in nutrient medium abundantly supplied with ammonia (Belimov et al 2001) which suggests that if sufficient nitrogen is provided to the bacteria, production of ACC deaminase is inhibited.…”
Section: Mechanisms For Growth Promotionmentioning
confidence: 99%
“…These include a wide range of soil bacteria forming less formal associations than the rhizobia-legume symbiosis; endophytes may stimulate plant growth, directly or indirectly, and include the rhizobia. Soil bacteria in the genera Rhizobium, Bradyrhizobium, Sinorhizobium, Mesorhizobium and Azorhizobium, belonging to the family Rhizobiaceae, invade plant root systems and form root nodules (Wang and Martinez-Romero 2000). Collectively, they are often referred to as rhizobia.…”
Section: Endophyticmentioning
confidence: 99%
See 1 more Smart Citation